A modelling approach to ascertain the memory induced by Findlater Jet in the Arabian Sea - Vikas Kumar Kushwaha; S Prasanna Kumar; F Feba; Lakshmi R. Shenoy; Abhisek Chatterjee; Ashok Karumuri (Climate Dynamics, 2026)
The formation of Findlater Jet (FJ) in the lower atmosphere over the Arabian Sea (AS) is an integral part of the Indian summer monsoon (ISM, June–September). Based on observations, our earlier study indicated that the FJ-induced heat signal during the ISM is potentially preserved in the upper ocean in the form of heat content in the southern AS until the following winter season. Through various sensitivity experiments with an ocean model, we could demonstrate the above and identify the processes that lead to the observed memory. We further demonstrate that the simulated mixed layer depth and the upper ocean heat content are higher in the southern AS during a flood monsoon year compared to a drought year. This is attributed to a relatively stronger FJ-induced wind stress curl during the flood summer monsoon, which deepens the thermocline and results in higher heat retention in the southern AS during the subsequent winter and spring seasons. The accumulated heat enhances pre-monsoon rainfall over the west Indian coastal region and, in turn, influences the ensuing monsoon rainfall.

Seismic Site Classification, Stratigraphy Assessment and SPT-Vs Correlation for Madhubani and Adjoining Regions of Bihar Based on In-Situ Geotechnical and MASW Investigations - Abhileen Chatterjee; Hrik Chaudhury; R. V. S. Jenny Laura; Aman Alok; Abhishek Kumar (Geotechnical and Geological Engineering, 2026)

Advanced workflows for UAV-based crop height estimation using structure from motion (SfM) point clouds - Sumantra Chatterjee; Bala Ram Sapkota; Gurjinder S. Baath; K. Colton Flynn; Douglas R. Smith (Remote Sensing Applications: Society and Environment, 2026)

Beyond the target: the ecotoxicological impact of flubendiamide in natural ecosystems - T. Roy; S. Ghosh; A. H. Mandal; N. C. Saha; S. Chatterjee; D. S. Paria; C. R. Multisanti; C. Faggio; S. Saha (International Journal of Environmental Science and Technology, 2026)

Enhancing LAI estimation using multispectral imagery and machine learning: A comparison between reflectance-based and vegetation indices-based approaches - Sumantra Chatterjee; Gurjinder S. Baath; Bala Ram Sapkota; K.Colton Flynn; Douglas R. Smith (Computers and Electronics in Agriculture, 2025)

Shelf-life extension of ready-to-cook Tilapia (Oreochromis spp.) fish balls using hurdle technology - Raj Kamal Gautam; Aarti S. Kakatkar; Ashika Debbarma; Prashant K. Mishra; Vivekanand Kumar; R Shashidhar; Suchandra Chatterjee (Food Bioscience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Assessment of groundwater level using satellite-based hydrological parameters in North-West India: A deep learning approach - Pranshu Pranjal; Dheeraj Kumar; Ashish Soni; R. S. Chatterjee (Earth Science Informatics, 2024)

A review on environmental impacts of renewable energy for sustainable development - D. Gayen; R. Chatterjee; S. Roy (International Journal of Environmental Science and Technology, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Unravelling the dynamics and causes of land subsidence in the National Capital Territory of Delhi, India, by spaceborne and in situ observations - R. S. Chatterjee; Pranshu Pranjal; Suresh Kannaujiya; Shailaja Thapa; Ashutosh Bhardwaj; Uma Kapoor; S. N. Dwivedi; Rajesh Chandra; Rajiv Kumar Srivastava; S. K. Singh; Harsh Kumar; Rajarshi Bhattacharjee; et al. (Bulletin of Engineering Geology and the Environment, 2023)

An evolving perspective on the fluoride mitigation techniques - S. K. Das; A. K. Pramanik; R. K. Das; A. Chatterjee (International Journal of Environmental Science and Technology, 2023)

Hydrated komatiites as a source of water for TTG formation in the Archean - R. Tamblyn; J. Hermann; D. Hasterok; P. Sossi; T. Pettke; S. Chatterjee (Earth and Planetary Science Letters, 2023)

Magmatic inflation, miniature dyke intrusion and prolonged torrential rainfall led to the emergence of the 2018 aseismic fissure in Kenya - R. S. Chatterjee; Kishan Kumar; Pranshu Pranjal; Suresh Kannaujiya; Prakash Chauhan (Natural Hazards, 2023)

Phlorotannins–bioactivity and extraction perspectives - Lekshmi R. G. Kumar; Preethy Treesa Paul; K. K. Anas; C. S. Tejpal; N. S. Chatterjee; T. K. Anupama; Suseela Mathew; C. N. Ravishankar (Journal of Applied Phycology, 2022)

Relic surface water (clay-pore water) input triggers arsenic release into the shallow groundwater of Bengal aquifers - Pousali Pathak; Prosenjit Ghosh; Sanchita Banerjee; R S Chatterjee; Noor Muzakkira; Pradip K Sikdar; Utsab Ghosal; Mao-Chang Liang; Kathiravan Meeran (Journal of Earth System Science, 2022)

Modelling the Spatial Variation of Methane and Nitrous Oxide Emission from Rice Fields Using DNDC Model - Rahul Tripathi; M. Majhi; S. G. Sahu; S. Mohanty; K. C. Moharana; Md Shahid; C. K. Swain; B. Lal; P. Gautam; P. K. Dash; D. Chatterjee; A. Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2021)

Seasonal Transport Pathway and Sources of Carbonaceous Aerosols at an Urban Site of Eastern Himalaya - Akansha Rai; Sauryadeep Mukherjee; Nikki Choudhary; Abhinandan Ghosh; A. Chatterjee; T. K. Mandal; S. K. Sharma; R. K. Kotnala (Aerosol Science and Engineering, 2021)

Genome‐wide variation in DNA methylation linked to developmental stage and chromosomal suppression of recombination in white‐throated sparrows - Dan Sun; Thomas S. Layman; Hyeonsoo Jeong; Paramita Chatterjee; Kathleen Grogan; Jennifer R. Merritt; Donna L. Maney; Soojin V. Yi (Molecular Ecology, 2021)
Much of our knowledge on regulatory impacts of DNA methylation has come from laboratory‐bred model organisms, which may not exhibit the full extent of variation found in wild populations. Here, we investigated naturally‐occurring variation in DNA methylation in a wild avian species, the white‐throated sparrow ( Zonotrichia albicollis ). This species offers exceptional opportunities for studying the link between genetic differentiation and phenotypic traits because of a nonrecombining chromosome pair linked to both plumage and behavioural phenotypes. Using novel single‐nucleotide resolution methylation maps and gene expression data, we show that DNA methylation and the expression of DNA methyltransferases are significantly higher in adults than in nestlings. Genes for which DNA methylation varied between nestlings and adults were implicated in development and cell differentiation and were located throughout the genome. In contrast, differential methylation between plumage morphs was concentrated in the nonrecombining chromosome pair. Interestingly, a large number of CpGs on the nonrecombining chromosome, localized to transposable elements, have undergone dramatic loss of DNA methylation since the split of the ZAL2 and ZAL2 m chromosomes. Changes in methylation predicted changes in gene expression for both chromosomes. In summary, we demonstrate changes in genome‐wide DNA methylation that are associated with development and with specific functional categories of genes in white‐throated sparrows. Moreover, we observe substantial DNA methylation reprogramming associated with the suppression of recombination, with implications for genome integrity and gene expression divergence. These results offer an unprecedented view of ongoing epigenetic reprogramming in a wild population.

Hybrid larval lethality of Drosophila is caused by parent-of-origin expression: an insight from imaginal discs morphogenesis of Lhr pausing rescue hybrids of D. melanogaster and D. simulans - R. N. Chatterjee; S. Kuthe; Piyali Chatterje (The Nucleus, 2021)

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

Backyard poultry farming for sustained production and enhanced nutritional and livelihood security with special reference to India: a review - U. Rajkumar; S. V. Rama Rao; M. V. L. N. Raju; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Use of IRS-1C and Its Follow-On Missions for Geological Applications: A Review - S. K. Srivastav; R. S. Chatterjee; Deepali Kapoor; G. Sreenivasan; E. V. R. Parthasaradhy (Journal of the Indian Society of Remote Sensing, 2021)

Genetic analysis of growth and egg production traits in synthetic colored broiler female line using animal model - L. Leslie Leo Prince; K. S. Rajaravindra; U. Rajkumar; B. L. N. Reddy; C. Paswan; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2020)

Assessment of Land Surface Subsidence Due to Underground Metal Mining Using Integrated Spaceborne Repeat-Pass Differential Interferometric Synthetic Aperture Radar (DInSAR) Technique and Ground Based Observations - Md Soyeb Alam; Dheeraj Kumar; R. S. Chatterjee; Vijay Upreti (Journal of the Indian Society of Remote Sensing, 2018)

A Chemosensitizer Drug: Disulfiram Prevents Doxorubicin-Induced Cardiac Dysfunction and Oxidative Stress in Rats - Varsha K. Sonawane; Umesh B. Mahajan; Sachin D. Shinde; Subhajit Chatterjee; Sandip S. Chaudhari; Harshada A. Bhangale; Shreesh Ojha; Sameer N. Goyal; Chanakya N. Kundu; Chandragouda R. Patil (Cardiovascular Toxicology, 2018)

Evidence for the existence of Persian Gulf Water and Red Sea Water in the Bay of Bengal - Vineet Jain; D. Shankar; P. N. Vinayachandran; A. Kankonkar; Abhisek Chatterjee; P. Amol; A. M. Almeida; G. S. Michael; A. Mukherjee; Meenakshi Chatterjee; R. Fernandes; R. Luis; et al. (Climate Dynamics, 2017)

Sequence Determination of an Antioxidant Peptide Obtained by Enzymatic Hydrolysis of Oyster Crassostrea madrasensis (Preston) - K. K. Asha; K. R. Remya Kumari; K. Ashok Kumar; Niladri S. Chatterjee; R. Anandan; Suseela Mathew (International Journal of Peptide Research and Therapeutics, 2016)

Assessing current genetic status of the Hainan gibbon using historical and demographic baselines: implications for conservation management of species of extreme rarity - J. V. Bryant; D. Gottelli; X. Zeng; X. Hong; B. P. L. Chan; J. R. Fellowes; Y. Zhang; J. Luo; C. Durrant; T. Geissmann; H. J. Chatterjee; S. T. Turvey (Molecular Ecology, 2016)
Evidence‐based conservation planning is crucial for informing management decisions for species of extreme rarity, but collection of robust data on genetic status or other parameters can be extremely challenging for such species. The Hainan gibbon, possibly the world's rarest mammal, consists of a single population of ~25 individuals restricted to one protected area on Hainan Island, China, and has persisted for over 30 years at exceptionally low population size. Analysis of genotypes at 11 microsatellite loci from faecal samples for 36% of the current global population and tissue samples from 62% of existing historical museum specimens demonstrates limited current genetic diversity ( Na = 2.27, Ar = 2.24, H e = 0.43); diversity has declined since the 19th century and even further within the last 30 years, representing declines of ~30% from historical levels ( Na = 3.36, Ar = 3.29, H e = 0.63). Significant differentiation is seen between current and historical samples ( F ST = 0.156, P = 0.0315), and the current population exhibits extremely small N e (current N e = 2.16). There is evidence for both a recent population bottleneck and an earlier bottleneck, with population size already reasonably low by the late 19th century (historical N e = 1162.96). Individuals in the current population are related at the level of half‐ to full‐siblings between social groups, and full‐siblings or parent–offspring within a social group, suggesting that inbreeding is likely to increase in the future. The species' current reduced genetic diversity must be considered during conservation planning, particularly for expectations of likely population recovery, indicating that intensive, carefully planned management is essential.

Detecting, mapping and monitoring of land subsidence in Jharia Coalfield, Jharkhand, India by spaceborne differential interferometric SAR, GPS and precision levelling techniques - R S Chatterjee; Shailaja Thapa; K B Singh; G Varunakumar; E V R Raju (Journal of Earth System Science, 2015)

Intersex (ix) mutations of Drosophila melanogaster cause nonrandom cell death in genital disc and can induce tumours in genitals in response to decapentaplegic (dpp disk ) mutations - R. N. CHATTERJEE; P. CHATTERJEE; S. KUTHE; M. ACHARYYA-ARI; R. CHATTERJEE (Journal of Genetics, 2015)

Role and Present Status of Biotechnology in Augmenting Poultry Productivity in India - C. Paswan; T. K. Bhattacharya; C. S. Nagaraj; R. N. Chatterjee; P. Guru Vishnu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

The high prevalence of serine protease autotransporters of Enterobacteriaceae (SPATEs) in Escherichia coli causing neonatal septicemia - R. Tapader; S. Chatterjee; A. K. Singh; P. Dayma; S. Haldar; A. Pal; S. Basu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Unsupervised and supervised classification of hyperspectral imaging data using projection pursuit and Markov random field segmentation - A. Sarkar; A. Vulimiri; S. Paul; Jawaid Iqbal; A. Banerjee; R. Chatterjee; S. S. Ray (International Journal of Remote Sensing, 2012)

Acute and chronic effects of endosulfan on the haemato-immunological and histopathological responses of a threatened freshwater fish, spotted murrel, Channa punctatus - Kamal Sarma; A. K. Pal; N. P. Sahu; R. S. Dalvi; Nirupama Chatterjee; S. C. Mukherjee; Kartik Baruah (Fish Physiology and Biochemistry, 2012)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

Effect of stocking density and journey length on the welfare of rohu (Labeo rohita Hamilton) fry - N. Chatterjee; A. K. Pal; T. Das; R. Dalvi; M. S. Mohammad; K. Sarma; S. C. Mukherjee; K. Baruah (Aquaculture International, 2010)

Proctolaclaps regalis usages Drosophila eggs and pupae as ovipositional substrate and their lifecycle closely mimics the life cycle of Drosophila - P. Chatterjee; S. Banerjee; R. N. Chatterjee (Proceedings of the Zoological Society, 2009)

Flood inundation modeling using MIKE FLOOD and remote sensing data - S. Patro; C. Chatterjee; S. Mohanty; R. Singh; N. S. Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2009)

Assaying Baseline Status of Particulate Laden Polyaromatic Hydrocarbon for a Grass Root Level Industrial Project - Girish Himatlal Pandya; N. Chatterjee; Ritesh Singh; Sanjay Kashyap; S. Pentu Saheb; S. R. Wate (Bulletin of Environmental Contamination and Toxicology, 2009)

Influence of progressive staling on germination of sugarcane - A. K. Shrivastava; S. Solomon; A. K. Srivastava; S. P. Shukla; A. Sawnani; R. Darash; C. Prajapati; Pushpa Singh; Priyanka Singh; R. K. Rai; R. Jain; Parul Srivastava; et al. (Sugar Tech, 2008)

Utilization of high resolution satellite gravity over the Carlsberg Ridge - S. Chatterjee; R. Bhattacharyya; T. J. Majumdar (Marine Geophysical Research, 2007)

Generation and study of high‐resolution satellite gravity over the Sumatran earthquake region - S. Chatterjee; R. Bhattacharyya; T. J. Majumdar (International Journal of Remote Sensing, 2007)

Transgenic Indian mustard (Brassica juncea) expressing tomato glucanase leads to arrested growth of Alternaria brassicae - Kalyan K. Mondal; R. C. Bhattacharya; K. R. Koundal; S. C. Chatterjee (Plant Cell Reports, 2007)

Phytotoxic Effect of Coal Mine Effluent on Growth Behavior, Betabolic Changes, and Metal Accumulation in Rice Plants (Oryza sativa L.) c.v. IR-36 - K. K. Tiwari; S. Dwivedi; U. N. Rai; A. K. Pandey; C. Chatterjee; N. K. Singh; R. D. Tripathi (Bulletin of Environmental Contamination and Toxicology, 2006)

Removal of carboxymethyl cellulase activity from the culture filtrate of Termitomyces clypeatus producing xylanase - A.K. Ghosh; M.L. Jana; A.K. Naskar; R. Chatterjee; S. Sengupta (Biotechnology Letters, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Impact of Carbofuran in the Oocyte Maturation of Catfish, Heteropenustes fossilis (Bloch) - S. Chatterjee; A. B. Dutta; R. Ghosh (Archives of Environmental Contamination and Toxicology, 1997)

Zinc and iron as bioindicators of precancerous nature of oral submucuos fibrosis - R. R. Paul; J. Chatterjee; A. K. Das; S. K. Dutta; D. Roy (Biological Trace Element Research, 1996)

Effects of L-ascorbic acid supplementation on dieldrin toxicity in rats - S. K. Bandyopadhyay; R. K. Tiwari; A. Mitra; B. Mukherjee; A. Banerjee; G. C. Chatterjee (Archives of Toxicology, 1982)